Dimensional differences in mandibular antegonial notches in temporomandibular joint ankylosis - Stuti Singh; Sumit Kumar; Rahul Pandey; Deepak Passi; Divya Mehrotra; Shadab Mohammad (Journal of Oral Biology and Craniofacial Research)
ABSTRACT: Background: Deep antegonial notch (AN) is seen in congenital and acquired abnormalities of mandible like condylar hypoplasia, temporomandibular joint ankylosis (TMA), muscular hypoactivity and brachial arch syndrome. This study was planned with an aim to study the depth of AN in TMA and find its relation with the duration of ankylosis. Materials and Methods: The study comprised 20 cases of unilateral or bilateral TMA, with age range 8–25 years. A comparison between ipsilateral and contralateral AN was done on orthopantomograms of these bilateral and unilateral cases with the time period of total duration of ankylosis. Results: Seven cases had right-sided ankylosis, six had left and seven had bilateral TMA where the history of ankylosis ranged from 6 months to 12 years. Spearman's rank correlation indicated a strong correlation between the duration of history of ankylosis and AN on the ipsilateral/contralateral sides. Wilcoxin signed rank test proved the results to be statistically significant. Conclusion: Deep accentuated AN is one of the clinical features of the TMA and has a direct relation to the morphology and growth pattern of mandible.